2022
DOI: 10.3847/1538-4357/ac78ee
|View full text |Cite
|
Sign up to set email alerts
|

New Theoretical Period–Luminosity–Metallicity Relations for RR Lyrae in the Rubin-LSST Filters

Abstract: The revolutionary power of future Rubin-LSST observations will allow us to significantly improve the physics of pulsating stars, including RR Lyrae. In this context, an updated theoretical scenario predicting all the relevant pulsation observables in the corresponding photometric filters is mandatory. The bolometric light curves are based on a recently computed extensive set of nonlinear convective pulsation models for RR Lyrae stars, covering a broad range of metal content, and have been transformed into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…the cases of Sculptor and Eridanus by Martínez-Vázquez et al 2016. Metal-dependent PW relations have also been derived for RR Lyrae, with the minimum metallicity effect corresponding to some combination of optical filters, such as B,V , that is predicted to be metal-insensitive, or g,r (see Marconi et al 2015Marconi et al , 2022. Moreover, the predicted metallicity dependence of RR Lyrae NIR PL and PW relations is in agreement with observations in Galactic globular clusters (see Bhardwaj et al 2023).…”
Section: Recent Results For Rr Lyrae Starssupporting
confidence: 68%
“…the cases of Sculptor and Eridanus by Martínez-Vázquez et al 2016. Metal-dependent PW relations have also been derived for RR Lyrae, with the minimum metallicity effect corresponding to some combination of optical filters, such as B,V , that is predicted to be metal-insensitive, or g,r (see Marconi et al 2015Marconi et al , 2022. Moreover, the predicted metallicity dependence of RR Lyrae NIR PL and PW relations is in agreement with observations in Galactic globular clusters (see Bhardwaj et al 2023).…”
Section: Recent Results For Rr Lyrae Starssupporting
confidence: 68%
“…Similarly, we obtained 〈μ〉 = 17.58 ± 0.15 mag for UMaII-V1, and it is in good agreement with the estimated value given by Zucker et al (2006;∼17.5 ± 0.3 mag), based on the isochrone fitting, and is almost the same as the one determined in Vivas et al (2020;17.60 ± 0.20 mag) when including additional RR Lyrae for UMaII. We also found statistically consistent distance measurements to these two dwarf galaxies if independent theoretical PWZ relations from Marconi et al (2015Marconi et al ( , 2022 were adopted instead of the empirical relations.…”
Section: The Distances Of the Two Rr Lyraesupporting
confidence: 59%
“…Since the light curves become more and more scattered as the distance increases, mainly in the u, z, and y bands, we showed that a good recovery (at least for optical bands) is possible for the RR Lyrae and the short-period Cepheids up to Leo I at 0.26 Mpc, as demonstrated by fitting parameters reported in Table 3. In particular, we derived an accurate mean magnitude with a precision two orders of magnitude lower than the rms of the theoretical PL and PW relations derived by Marconi et al (2022). We point out that, when propagating the uncertainties on the PL/PW relations to derive distances, usually the propagation on the uncertainties of the coefficients is vanishing, while the error on the mean magnitudes and extinction dominate, being at least an order of magnitude larger.…”
Section: Discussionmentioning
confidence: 78%
“…To prove our new metric potential, we first studied the recovery of pulsating variable stars' light curves in a selected sample of LG galaxies. In recent work (Marconi et al 2022), we have shown that the application of the period-luminosity-metallicity (PLZ) and period-Wesenheit-metallicity (PWZ) relations to future Rubin LSST observations of RR Lyrae in a massive stellar system will represent a powerful tool to derive mean and individual distances. To make these relations useful, the mean magnitudes that we include must be recovered with an accuracy comparable to or better than the rms of the relations (around 0.1; see column 5 of their Table 5).…”
Section: A Test Case: Pulsating Stars In Local Group Dwarf Galaxiesmentioning
confidence: 99%
See 1 more Smart Citation